Studi Perbandingan Jaringan Blockchain sebagai Platform Sistem Rating - Lathifah Arief; Tri A Sundara; Heru Saputra (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
In the tourism industry, reputation is important information that influence customer behavior. Some services, such as hotels, take advantage of feedback from customers. This research aims to develop a review system by utilizing blockchain and machine learning for sustainable tourism. As proof of concept, a comparison method is carried out between several existing Blockchain networks. The system prototype then implemented using Hyperledger blockchain network, so that measurement of its performance is possible. The results show the feasibility of the blockchain network to be used for a rating system, although several aspects need to be considered in its implementation.